Analisis Penanggulangan Balap Liar di Kalangan Remaja oleh Pemerintah Desa Sipin Teluk Duren - Karmelia, Mila; Maulia, Siti Tiara; Utami, Sundari (AHKAM, 2025)
Illegal street racing is a form of juvenile delinquency driven by curiosity, environmental influences, and limited recreational facilities, posing a serious problem in Sipin Teluk Duren Village, Kumpeh Ulu District. This activity, typically conducted by adolescents aged 13–18 on Saturday nights, causes public concern due to risks to safety and public order. This study aims to examine the village government’s efforts to combat illegal street racing and identify effective measures to create a safe environment that supports juvenile delinquency prevention. A descriptive qualitative approach was employed to provide an in-depth and contextual understanding of the phenomenon, with the researcher serving as the primary instrument. The findings reveal that mitigation efforts involve three approaches: pre-emptive, preventive, and repressive. Pre-emptive measures through counseling have yet to address the root causes specifically. Preventive efforts include alternative activities, but youth participation remains low and supervision is inadequate. Repressive actions, such as vehicle confiscation, are not accompanied by formal legal sanctions, limiting their deterrent effect. The study concludes that effective mitigation requires strengthened communication, community involvement, consistent social control, and synergy between village authorities and law enforcement through village regulations and routine patrols. The implications emphasize the importance of an integrated and sustainable approach to comprehensively prevent juvenile delinquency.